Turkish Efforts in Peacekeeping and the Introduction of the TUBAKOV Dataset: An Exploratory Analysis. Issue 4 (8th August 2018) - Yalçınkaya, Haldun; Hatipoglu, Emre; Açar, Dilaver Arıkan; Çelikpala, Mitat
ABSTRACT: This study introduces the TUBAKOV dataset, which offers extensive data on 57 peacekeeping operations (PKOs) that Turkey has contributed to between the years 1988–2015. TUBAKOV improves existing data in several ways. First, it draws data from governmental resources that have not been previously used. Second, Turkey's contributions for each PKO are presented both at the levels of PKO and PKO-contribution year format. The website of the dataset also allows access to qualitative data such as primary text sources, hence facilitating qualitative and multi-method research on peacekeeping. Preliminary analyses indicate that the frequency, nature and the geographic focus of Turkey's contributions to peacekeeping operations demonstrate a significant shift with the new millennium. Preliminary findings offer interesting insights to the changing characteristics of Turkey's PKO involvements relating to the content, geography and timing of these contributions over the time period covered by this dataset.